1995
DOI: 10.1209/0295-5075/31/7/008
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Structure of La 2 BaCuO 5 : A Magnetic Insulator

Abstract: The results of density functional calculations of the electronic structure of La2BaCu06 are presented. The calculations used the standard spin-polarized Local Density Approximation. The system is found to be a strong ferromagnet and has an insulating ground state. The results of the calculations show excellent agreement with the electronic configurations, magnetic ordering, and the localized magnetic moments inferred from experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…6 in Ref. 12). The mirror image of the minority spin band with respect to the Fermi energy corresponds to the hole band with minority spin in the Bogoliubov-de Gennes picture.…”
Section: (B)mentioning
confidence: 91%
See 2 more Smart Citations
“…6 in Ref. 12). The mirror image of the minority spin band with respect to the Fermi energy corresponds to the hole band with minority spin in the Bogoliubov-de Gennes picture.…”
Section: (B)mentioning
confidence: 91%
“…Here we focus on La 2 BaCuO 5 (LBCO) [11] which is an important representative FI in spintronics. According to a first-principle band calculation [12], the bottom of the minority spin band is at the Γ point whose wave number is (k a , k b , k c ) = (0, 0, 0), where k j for j = a, b, and c is the wave number along j axis (see Fig. 6 in Ref.…”
Section: (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1990, Mizuno et al, found that LBCO undergoes a ferromagnetic transition at 5.2 K [24]. The exchange splitting ex V is estimated to be 0.34 eV by a first-principle band calculation using the spin-polarized local density approximation [27]. Since the exchange splitting is large and the bands are originally half-filled, the system becomes FI.…”
Section: Magnetic and Electronic Properties Of Ferromagnetic Insulatorsmentioning
confidence: 99%
“…The tight binding parameters t and g have been determined by fitting to the first-principle band structure calculations [27]. The formation of the π-junction can be experimentally detected by using a HTSC ring [see Fig.…”
Section: Josephson Current For High-c T Superconductorsmentioning
confidence: 99%